2013
DOI: 10.1097/gco.0b013e32835faae5
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes in patients with male infertility because of Klinefelter's syndrome, Kartagener's syndrome, round-head sperm, dysplasia fibrous sheath, and ‘stump’ tail sperm

Abstract: In Klinefelter's and Kartagener's syndrome, the fertilization potential and the live-birth rate are close to that obtained from nonspecific causes of sperm defects. Round-head sperm shows a lower fertility potential, but the addition of assisted oocyte activation and the use of intracytoplasmic morphologically selected sperm injection increased the rates of live birth. Conditions such as DFS and stump tail have a poor prognosis, but the number of cases described in the literature is too limited for drawing fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…To date, there is no evidence that pregnancy success rate may be different in globozoospermic patients with different mutational status. Many studies using ICSI for patients with globozoospermia reported low fertilization, pregnancy and live‐birth rates . The first explanation is the reduction or absence of the phospholipase C zeta (PLCζ), a testis‐specific phospholipase involved in the oocyte activation .…”
Section: Abnormalities Of the Sperm Headmentioning
confidence: 99%
“…To date, there is no evidence that pregnancy success rate may be different in globozoospermic patients with different mutational status. Many studies using ICSI for patients with globozoospermia reported low fertilization, pregnancy and live‐birth rates . The first explanation is the reduction or absence of the phospholipase C zeta (PLCζ), a testis‐specific phospholipase involved in the oocyte activation .…”
Section: Abnormalities Of the Sperm Headmentioning
confidence: 99%
“…The various flagellar anomaly phenotypes associated with genetic mutations have already been described as ‘short tails’, ‘stump tails’ or ‘dysplasia of the fibrous sheath’ (Neugebauer et al ., ; Chemes et al ., ; Davila Garza & Patrizio, ). Ben Khelifa et al .…”
Section: Resultsmentioning
confidence: 99%
“…Spermatozoa with defect in head–tail attachment showed low fertility potential; the arrest of early embryo development can be a consequence of centriole defective function (Chemes et al., ; Rawe et al., , ) or low chromatin and DNA quality (Rondanino et al., ); in a few cases, the pregnancies were obtained probably because the injected sperm head was equipped with a normal centriolar area (Gambera et al., ; Porcu et al., ). In conditions such as DFS, the reproductive outcome is poor, with low fertilisation and very few babies born (Dávila Garza & Patrizio, ). In any case, when these defects appear alone or when rarely are associated, the fertility potential is very low.…”
Section: Discussionmentioning
confidence: 99%